Androgens in Patients With Luminal B and HER2 Breast Cancer Might Be a Biomarker Promoting Anti-PD-1 Efficacy - Li, Peng; Yuan, Wenhui; Wu, Ruan; Zeng, Chuqian; Li, Ke; Lu, Ligong (Frontiers in Oncology, 2022)
Endocrine therapy is considered as an effective strategy for estrogen and progestogen receptor (ER and PR) positive breast cancer (BRCA) patients, whereas resistance to these agents is the major cause of BRCA mortality in women. Immune checkpoint receptors (ICRs) blockade is another approach to treat BRCA, but the response rate of this approach for non-triple negative breast cancer (non-TNBC) is relatively low. Recently, androgen receptor (AR) has been identified as a tumor suppressor in ER-positive BRCA; however, the relationship between the levels of androgens and ICRs on T cells in BRCA is unclear. We observed that testosterone and dihydrotestosterone (DHT) in patients with HER2 and Luminal B were significantly lower than in healthy controls, and the expression of AR has significant correlation with overall survival (OS) advantage for Luminal B patients. Besides, testosterone and DHT were positively correlated with the PD-1 expression on Vδ1+ T cells in HER2 and Luminal B patients. These results suggest a potential approach of combining androgens with PD-1 blockade for treating HER2 and Luminal B breast cancer.